Studies on the wastage of export grapes : with special reference to that caused by Botrytis cinerea, Pers. - Du Plessis, S. J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric)--Stellenbosch University, 1935.